Epidemiology of extrapulmonary tuberculosis in high-burden regions - E. V. Kulchavenya; M. M. Merganov; F. R. Sharipov (Туберкулез и болезни лёгких)
The objective of the study: to assess the structure of extrapulmonary tuberculosis in two high-burden regions (Siberia, the Far East of the Russian Federation, and the Republic of Tajikistan), with the consideration of HIV status, gender, and age of patients. Subjects and methods. A simple cohort open retrospective study was carried out based on the analysis of statistical reports from TB control institutions of the Republic of Tajikistan, Siberian and Far Eastern Federal Districts of the Russian Federation for 2018. Results. In the Siberian Federal District and Far Eastern Federal District, among extrapulmonary forms of tuberculosis, the proportion of bone and joint tuberculosis made 43.6%, urinary tuberculosis – 21.3%, and tuberculosis of central nervous system ranked third and made 17%. In Tajikistan, bone and joint tuberculosis also prevailed and made 46.0%, followed by tuberculosis of peripheral lymph nodes. In Tajikistan, among extrapulmonary tuberculosis patients, HIV positive patients made only 3.5%, while in the Siberian and Far Eastern Federal Districts, they made 36.8%. However, in the Siberian and Far Eastern Federal Districts of the Russian Federation, among HIV positive patients with extrapulmonary tuberculosis, tuberculosis of the central nervous system (38.3%) prevailed, in the Republic of Tajikistan it was tuberculosis of peripheral lymph nodes (37.9%), followed by bone and joint tuberculosis (31.0%) and abdominal tuberculosis (17.2%). Urogenital tuberculosis was in the last place in the structure of extrapulmonary tuberculosis in HIV-positive patients.